Post-Haiyan assessment of the abundance and density of Bohadschia marmorata in the Marine Protected Areas (MPAs) of Guiuan, Eastern Samar and Palompon, Leyte Philippines - Yutangco, Anne Janeen A. (2016)
Bohadschia marmorata, along with other sea cucumber species, have been known to inhabit the marine protected areas in Guiuan and Palompon. However, they are vulnerable to extreme conditions. This study collected data on the abundance and density of Bohadschia marmorata in two Marine Protected Areas in Guiuan Eastern Samar and Palompon Leyte after the typhoon Haiyan. This was conducted by establishing and sampling transect belts with areas of 250 meter square in one chosen station for each site supplemented by time-hand-picking of B. marmorata individuals on three stations. A previous study conducted in 2012 showed an average monthly density value of 0.053 plus or minus 0.012 in Guiuan whereas average station densities in Guiuan and Palompon were 63 plus or minus 45.85 and 2.2 plus or minus 0.65, respectively. Present study assessed the same areas and stations obtaining a monthly density value of 0.048 plus or minus 0.004 in Guiuan which shows 9% decrease in the density values within the four-year gap. Monthly average station densities for both Guiuan and Palompon were collected to be 13 plus or minus 4.44 and 1.8 plus or minus 0.21, respectively which shows density decrease of 79% for Guiuan and 18% for Palompon. The marine protected area in Guiuan Eastern Samar has higher Bohadschia marmorata density values than the marine protected area in Palompon transect and station-wise and that the Bohadschia marmorata densities have decreased from 2012 to 2015.